2019
DOI: 10.1590/1518-8345.2838.3160
|View full text |Cite
|
Sign up to set email alerts
|

Tendência e distribuição espacial de doenças infecciosas em gestantes no estado do Paraná-Brasil

Abstract: Objetivo analisar a tendência e a distribuição espacial de algumas doenças de notificação compulsória em gestantes. Método estudo ecológico, com dados do Sistema Nacional de Agravos de Notificação, das incidências das seis doenças de notificação mais frequentes em gestantes. O modelo de Prais-Winsten foi utilizado para a análise da tendência classificada em estável, decrescente e crescente, segundo macrorregiões. Para a análise espacial, foram calculadas as incidências distribuídas em percentis, em mapas co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…Apesar de serem parâmetros de grande valia na análise de qualidade dos acompanhamentos prestados nas unidades do município, a ausência desses dados não diminui a observação do descaso com que tem se tratado essa patologia, já que a mínima parcela de parceiros tratados evidencia o perigo de reexposição da gestante à contaminação e à possibilidade de uma gestação culminar em sífilis congênita. As falhas na assistência do pré--natal, a realização do diagnóstico tardio ou um tratamento inadequado, são fatores importantes e explicam os motivos pelos quais ainda existe um elevado número de casos de sífilis congênita 13 . Vale destacar também que as medidas de prevenção da doença são simples e de baixo custo, enquanto o tratamento de uma criança com sífilis congênita é bastante prolongado e oneroso 5 .…”
Section: Methodsunclassified
“…Apesar de serem parâmetros de grande valia na análise de qualidade dos acompanhamentos prestados nas unidades do município, a ausência desses dados não diminui a observação do descaso com que tem se tratado essa patologia, já que a mínima parcela de parceiros tratados evidencia o perigo de reexposição da gestante à contaminação e à possibilidade de uma gestação culminar em sífilis congênita. As falhas na assistência do pré--natal, a realização do diagnóstico tardio ou um tratamento inadequado, são fatores importantes e explicam os motivos pelos quais ainda existe um elevado número de casos de sífilis congênita 13 . Vale destacar também que as medidas de prevenção da doença são simples e de baixo custo, enquanto o tratamento de uma criança com sífilis congênita é bastante prolongado e oneroso 5 .…”
Section: Methodsunclassified
“…Prais–Winsten linear regressions were used between 2006 and 2015, a statistical procedure for the analysis of prevalence trend regression and autocorrelation in time series (Falavina et al ., 2019). It was used for annual increment rates and respective confidence intervals (95%).…”
Section: Methodsmentioning
confidence: 99%
“…Viral hepatitis is caused by different etiological agents and have tropism for the liver tissue, presenting diversified clinical pictures and own transmission mechanisms, being the types B and C parenteral, especially sexual. [1][2][3][4][5][6][7][8][9][10][11][12] Currently, hepatitis is a serious public health challenge worldwide, highlighting the types B and C for presenting a tendency to increase incidence. 2 According to the 2019 epidemiological bulletin of viral hepatitis, in recent decades Brazil has notified more than 632,814 confirmed cases of hepatitis and of these, a total of 233,027 (36.8%) were type B (HBV) and 228,695 (36.1%) type C (HCV).…”
Section: Introductionmentioning
confidence: 99%
“…6 To circumvent this problem, the spatial analysis of diseases has been used, because this method allows the evaluation of the places of greatest epidemiological pressure, helping to understand the factors that contribute to the situation. [7][8] The objective is not to investigate the disease in individuals, but to answer the causes of disease incidence by comparing different contexts in order to understand how a social determinant affects the health of a population group. 8 From this perspective, this study was designed to analyze the spatial and epidemiological distribution of reported cases of hepatitis B and C from 2012 to 2016 in the municipality of Caxias, Maranhão, so that it can offer professionals and managers the vision of how the use of new technologies during health planning can assist in decisions consistent with the population needs of regions with higher prevalence for these diseases.…”
Section: Introductionmentioning
confidence: 99%